LESS COMMON PATTERNS WITH INTENSIFIERS ‘TOO’ AND ‘VERY IN THE CORPUS OF INUGURAL ADDRESSES OF US PRESIDENTS - Prihantoro, Prihantoro (Jurnal Pendidikan Bahasa dan Sastra, 2015)
Â AbstractThis paper studies â€œveryâ€ and â€œtooâ€, two intensifiers used in the corpus of inaugural address of all US presidents, from Washington to Obama. My aims here is to identify uncommon pattern with â€œtooâ€ and â€œveryâ€, and the semantic prosodies as well. I downloaded the data and processed it as a corpus by using a corpus tookit called AntConc (Anthony, 2006). I used the query â€œveryâ€ and â€œtooâ€ to obtain concordances. A shared feature of these intensifiers is they mostly modify adjectives as shown by frequency. Although less significant in terms of frequency, some common patterns are discovered, such as â€œvery + Nâ€ and â€œvery + AdjSuperlative + Nâ€ construction, which are attested in COCA. One that is against prescriptive grammar is a + too + Adj + Nâ€, where the suggested construction is usually â€œtoo + Adj + a + Nâ€. As for the semantic prosody, I found some data attested in COCA, where â€œtooâ€ can be used to intensify positive evaluation, which is contrary to Azar (2002) and some other grammar books. As for very, it is more flexible that the prosodies might either be positive or negative. The result of COCA and BNC has shown that these structures are uncommon. I argue that these structures are used under the markedness frame, to make listeners focus on issues that the speakers wanted to empahasize.Keywords: very, too, intensifiers, semantic prosody, inaugural address, corpusÂ AbstrakArtikel ini menyelidiki "very" dan "too", dua pengintensif yang ditemukan dalam korpus pidato pelantikan semua presiden AS, dari Washington sampai Obama. Tujuan artikel ini adalah untuk mengidentifikasi pola tidak biasa dengan kata "very" dan "too", dan prosodi semantiknya. Saya mengunduh data pidato dan diproses sebagai korpus dengan menggunakan perangkat korpus yang disebut AntConc (Anthony, 2006). Saya menggunakan query "very" dan "too" untuk mendapatkan konkordansi. Fitur yang ditemukan dari kedua pengintensif ini adalah keduanya kebanyakan memodifikasi kata sifat seperti yang ditunjukkan oleh frekuensi. Meskipun kurang signifikan dalam hal frekuensi, beberapa pola umum ditemukan, seperti konstruksi "very+ N" dan "too+ AdjSuperlatif + N", yang dibuktikan dalam COCA. Salah satu fitur yang bersebrangan dengan tata bahasa preskriptif adalah pola â€œa + too+ Adj + N ", sementara konstruksi yang biasa dipakai adalah " too+ Adj + a + N ". Adapun secara prosodi semantik, saya menemukan beberapa data yang dibuktikan di COCA, di mana "too" dapat juga digunakan untuk mengintensifkan penilaian positif, yang bertentangan dengan Azar (2002) dan beberapa buku tata bahasa lainnya. Sementara itu, kata â€œveryâ€ lebih fleksibel di mana prosodinya bisa positif atau negatif. Hasil COCA dan BNC menunjukkan bahwa struktur ini jarang ditemukan. Saya berpendapat bahwa struktur ini digunakan di bawah bingkai markedness, untuk membuat pendengar berfokus pada isu-isu yang ingin ditekankan penutur.Kata kunci: very, too, pengintensif, prosodi semantik, pidato pelantikan, korpus